Math
posted by Christine .
Can someone please check my answers below for accurateness? The instructions are: Differentiate and simplify.
1) y=(2x^2+3x1)(3x^25x3)
y'=(4x+3)(3x^25x3)+(2x^2+3x1)(6x5)
2) y=(5x^2+3x1)(3x^25x3)
y'=(10x+3)(4x^23)+(5x^2+3x1)(8x)
3)y=6x^37x^2+5x7+x^(5/3)7/(x^3)
y'=18x^214x+5+5x^(2/3)+21/(x^4)
4) y=[5x^43x^3+6x^25x+7x^(3/2)]/x^2
y'=10x3+5/(x^2)14/(x^3)+1/(2((sqrt)x)^3)
5) y=(5x^23x+7)(3x^2+7x2)(6x^2+4x5)
y'=(10x3)(3x^2+7x2)(6x^2+4x5)+(5x^23x+7)(6x+7)(6x^2+4x5)+(5x^23x+7)(3x^2+7x2)(12x+4)
6) y=(7x^35x^2+6x3)^12
y'=12(21x^210x+6)(7x^35x^2+6x3)^11
7) y=(4x^2+3)^5(2x^21)^4
y'=[8x(4x^2+3)^4(2x^21)^3][5(2x^21)+2(4x^2+3)]
8) y=(4x^2+3x5)^(4/5)
y'=[4(8x+3)]/[5(4x^2+3x5)^(1/5)]
O.K. Bold the wrong answers or let me know which ones I should double check and fix. Thanks for your help and I really appreciate it because there are no answers to these questions in the back of the book, so I need to know if they are correct. Thank you once again!

On number 2, I believe you copied the question incorrectly.
Many of the problems can be simplified by foiling and adding terms (#1, 2 for example) 
#2 is completly wrong
#3 has the wrong coefficent for the x^(2/3) term
#7 looks suspicious 
#7 is correctly differentiated and simplified